Pengaruh Pemberian Biskuit Ubi Ungu Dan Biskuit (PMT) Terhadap Penambahan Lingkar Lengan Atas Ibu Hamil KEK - Marisa, Walidatun; Sunarsih, Sunarsih; Utami, Vida Wira (MIDWIFERY JOURNAL, 2023)
Background: Nutritional problems experienced by pregnant women in Indonesia are chronic energy deficiency (CED). Pregnant women who experience CED will be able to cause babies born with low birth weight, prematurity, miscarriage, difficult labor, post partum bleeding and congenital defects. Avoiding that matters, additional nutrition for pregnant women is given in the form of additional food. Additional food is given to pregnant women to increase their daily nutritional needs. One of the foods that contain carbohydrates source which is quite important in our food security is sweet potato. The purpose: the study was to determine the effect of giving purple sweet potato with the nutritional status in the third trimester of pregnant women in the working area of Tri Karya Mulya Health Center Mesuji Regency in 2021.Methods: This research type is quantitative with a Quasi-experimental research design. The population/subjects taken in this research were pregnant women in the third trimester. The research was planned in the Working Area of Tri Karya Mulya Public Health Center, Mesuji Regency in 2021, the object of this research was the giving of purple sweet potato with the nutritional status of pregnant women. It was held in March - April 2021. The data collection used observation sheets. The data analysis was univariate and bivariate (t-test).The results: showed that the nutritional status before being given PMT + purple sweet potato was 20.6 cm and after being given PMT + sweet potato was 22.0 cm. The nutritional status before being given PMT was 20.1 cm and after being given PMT was 20.8 cm. Conclusion: There is an effect of giving purple sweet potato with the nutritional status of pregnant women TM II in the Work Area of the Tri Karya Mulya Public Health Center, Mesuji Regency in 2021 with a value (P value = 0.000). Suggestions: for health workers, especially midwives, to be able to increase activities based on local wisdom by planting sweet potatoes in every yard at home Keywords : Purple Sweet Potatoes and Nutritional Status of Pregnant Women ABSTRAK Latar Belakang: Masalah gizi yang dialami ibu hamil di Indonesia adalah kekurangan energi kronis (KEK). Ibu hamil yang mengalami KEK akan dapat menyebabkan bayi lahir dengan berat badan lahir rendah, prematuritas, keguguran, persalinan sulit, perdarahan post partum dan cacat bawaan. Untuk menghindarinya maka diberikan tambahan gizi bagi ibu hamil berupa makanan tambahan. Salah satu makanan yang mengandung sumber karbohidrat adalah ubi jalar.Tujuan penelitian: diketahui pengaruh pemberian ubi jalar ungu dengan status gizi ibu hamil TM II Di Wilayah Kerja UPT  Puskesmas Tri Karya Mulya Kabupaten Mesuji tahun 2021.Metode: Jenis penelitian kuantitatif desain penelitian Quasi eksperimen. Populasi adalah ibu hamil TM II di Wilayah Kerja UPT  Puskesmas Tri Karya Mulya Kabupaten Mesuji, sebanyak 48 ibu hamil  KEK, dengan jumlah sampel 30 yang dibagi menjadi 2 kelompok. Telah dilaksanakan pada bulan Maret - April  2021. Objek dalam penelitian ini adalah pemberian ubi jalar ungu dan status gizi ibu hamil.  Pengumpulan data menggunakan lembar observasi. Analisis data secara univariat dan bivariat (uji t).Hasil penelitian: diketahui status gizi sebelum diberikan PMT + ubi jalar ungu adalah 20,6 cm dan setelah diberikan PMT + Ubi jalar adalah 22,0 cm.status gizi sebelum diberikan PMT adalah 20,1 cm dan  setelah diberikan PMT adalah 20,8 cm.Kesimpulan: Ada pengaruh pemberian ubi jalar ungu dengan status gizi ibu hamil TM II Di Wilayah Kerja UPT Puskesmas Tri Karya Mulya Kabupaten Mesuji Tahun 2021dengan nilai (P value = 0,000).Saran: bagi tenaga kesehatan khususnya bidan untuk dapat meningkatkan kegiatan berbasis kearifan lokal dengan menanam ubi jalar di setiap perkarangan di rumah. Kata Kunci : Ubi jalar Ungu dan Status Gizi Ibu Hamil